Links between the Provisions of Social Work and Education Science in the Socialisation of the Disabled - Vaicekauskienė, Violeta (Pedagogika, 2016)
The article reveals the theoretical conception of the construct of socialisation as well as the process and nature of the process of its practical implementation that is directed to meet globalisation challenges, i.e. sustainable and accordant development ensuring the well-being of communities and individuals, as well as life quality. Hence, the priorities of the socialization of disabled people is changing focusing on the development of inclusion and participation in social life as well as striving for more rapid development and socialisation of the disabled. Social sciences, including educational science, social pedagogy and social work that is relatively new as it has lasted for a decade in Lithuania, search for solutions enabling to efficiently employ connections between them in solving problems of socialisation implementation. The article presents empirical research that involved 10 participants and included a semi-structured group interview. The participants have a qualification of a social pedagogue acquired in BA studies and have accomplished MA studies in the field of social work at Lithuanian University of Educational Sciences; they implement practical social work with different groups of the disabled. The research results were generalised and interpreted using content analysis method that is based on “the measurement of the frequencies of quality categories” (Bitinas, 2006, 275). The group discussion method was employed to discuss socialisation problems of the disabled and it embraced three groups of questions: the first group covered the selection and definition of the conceptions and approaches of socialisation, as well as the prevailing paradigms of science and socialisation,; the second group incorporated achievements in socialisation implementation and identification of its prevailing strategies and methods; whereas the third group dealt with the anticipation of socialisation factors and distracters, as well as the possibilities and prospects of their elimination. The following conclusions are drawn: 1) under the conditions of modern socialization implementation, the diversity of the paradigms of socialisation process and their conceptions become of topical importance as they reveal the connections between experts of education and social work. They are manifested through: a) holistic approach towards socialisation by both sciences, which is especially relevant for the socialisation of the disabled that is determined by the developmental disorders of individual persons; b) the specifics of the implementation of functional goals of the systems of every science correlate with the spectrum of the employed paradigms; c) the paradigms of social work are directed towards and reflect globalisation challenges to a greater extent; 2) when identifying the factors of socialisation implementation, the experts give an identical evaluation of the aspects of educational and social work socialisation distinguishing the creation of an integrative environment and cooperation in it, application of the diversity of specialists’ professionalism and work methods, ensuring of activity and rehabilitation possibilities and measures in regard to the functional requirements of science systems; 3) it is important and essential to develop interdisciplinary tendencies of cooperating social work and educational science and search for effective means of its expression in the socialisation of disabled people.